THE EFFECT OF INTERCROPPING MODEL AGAINTS WHEAT AND TABACCO GROWTH AND PRODUCTION - Alfna Handayani (Widyariset, 2011)
The aim of this research was to study the effect of intercropping model against wheat and tobacco pro-duction. The experiment was conducted in Kaliangrik-Kabupaten Magelang, Samiran-Kabupaten Boyolali, Kledung-Kabupaten Temanggung from April 2010 to October 2010.The experiment was arranged in Random-ized Completed Block Desain consisted of 3x3+2 control with 5 replications. The fi rst factor were 3 location (Kaliangkrik, Samiran, Kledung). The second factor were 3 model wheat-tobacco intercropping, i.e: model I: tobacco population is constant with wheat planted in two other sides of tobacco, model II Tobacco population is constant with wheat planted only in one side, model III tobacco population is decreased a half and is replaced by wheat population (50%). In general the most efi sien model in Kaliangkrik-Magelang was model III (50%), Samiran-Boyolali was model II (one side), and Kledung Temanggung were both model II (one side) and model III (50%) showed the highest value.